Rationalising development of classification systems describing livestock production systems for disease burden analysis within the Global Burden of Animal Diseases programme - Yin Li; McIntyre, K. Marie; Rasmussen, Philip; Gilbert, William; Chaters, Gemma; Raymond, Kassy; Jemberu, Wudu T.; Larkins, Andrew; Patterson, Grace T.; Kwok, Stephen; Kappes, Alexander James; Mayberry Dianne; et al. (Elsevier, 2024)
The heterogeneity that exists across the global spectrum of livestock production means that livestock productivity, efficiency, health expenditure and health outcomes vary across production systems. To ensure that burden of disease estimates are specific to the represented livestock population and people reliant upon them, livestock populations need to be systematically classified into different types of production system, reflective of the heterogeneity across production systems.